Estudo do desenvolvimento da formulação de um xampu sem sulfatos - Castro, Iana Lívia de Oliveira (Universidade Federal Rural do Semi-Árido, 2018)
The change of habits and the influence of the media in having a stereotype of defined bodies, exacerbated vanity, and health care led to the cosmetics market undergoing major transformations, among them, the use of alternative sources for the production of shampoos without surfactants and free of petroleum derivatives. This work aims to address the development and study for the manufacture of a sulfate-free shampoo, where samples were tested and physicochemical and organoleptic analyzes were carried out, and it is possible to conclude that the studies for a sulfate-free shampoo formulation are consistent and that it is possible to develop a shampoo with the same emollience, foam and softness of conventional shampoos.
Relatório
Keywords: Xampu sem sulfatos; Cosméticos; Derivados do petróleo; Sulfate-free shampoo; Cosmetics; Petroleum derivatives; ENGENHEARIAS::ENGENHARIA QUIMICA